A cost-effective and ecological stochastic optimization for integration of distributed energy resources in energy networks considering vehicle-to-grid and combined heat and power technologies. (January 2023) - Daramola, Alex S.; Ahmadi, Seyed Ehsan; Marzband, Mousa; Ikpehai, Augustine
Abstract: Electric vehicles (EVs) have the potential to decarbonize the transport sector and contribute to the attainment of the global Net-Zero goal. However, to achieve sustainable decarbonization, EVs' power for grid-to-vehicle (G2V) operations should be sourced from carbon-free or low carbon power generating sources. Whilst the adoption of renewable energy sources (RES) in EVs' G2V process has been extensively explored, combined heat and power (CHP) technologies are underexamined. Hence, this paper deploys harmonized natural gas and fuel cell CHP technologies alongside RES and battery energy storage systems (BESS) to facilitate EVs' G2V and vehicle-to-grid (V2G) operations. While the BESS supports V2G operations and stores excess power from the CHP and RES, the CHP's by-product heat could be employed in heating homes and industrial facilities. Furthermore, to maximize environmental and economic benefits, the CHP technologies are designed following the hybrid electric-thermal load strategy, such that the system autonomously switches between following the electric load strategy and following the thermal load strategy. The proposed optimization problem is tested using three different case studies (CSs) to minimize the microgrid's (MG) operating costs and carbon dioxide ( CO 2 ) emissions in a stochastic framework considering the RES generations, the load consumption, and the behaviour patterns of charging/discharging periods of EVs as the uncertain parameters. The first CS tests the proposed algorithm using only CHP technologies. Secondly, the algorithm is examined using the CHP technologies and RES. Finally, the BESS is added to support and analyse the impacts of the V2G operations of EVs on the MG. Furthermore, the life cycle assessment is investigated to analyse the CO 2 emissions of distributed generations. The results show a 32.22%, 44.49%, and 47.20% operating cost reduction in the first, second, and third CSs. At the same time, the CO 2 emissions declined by 29.13%, 47.13% and 47.90% in the various corresponding CSs. These results demonstrate the economic and environmental benefits of applying CHP with RES in facilitating G2V and V2G operations towards achieving a decarbonized transport sector. Highlights: Minimizing operating cost and carbon emission in a stochastic operation framework. Investigating the life cycle assessment for calculating the CO2 emissions. Employ hourly cost-based G2V and V2G strategies to support energy networks. Investigate BESS's economic and environmental contributions in aiding V2G facility. Formulate and model a harmonized natural gas and fuel cell CHP system.